Path Analysis of Vocational Education Cooperation and Development in the Greater Bay Area from the Perspective of the Qualifications Framework (Journal of Global Humanities and Social Sciences, 2024)
Vocational education has an irreplaceable role in cultivating high-quality talents adapted to the needs of modern industries, promoting flexible employment in the labor market, and promoting the sustainable development of the regional economy. However, due to the differences in the education system, qualifications, and curriculum between regions, there are many problems in vocational education in the Greater Bay Area that need to be solved. Based on this, this paper analyzes in detail the functions and roles of the QF (qualifications framework) in vocational education, and by comparing and analyzing the characteristics and current situation of vocational education in each region, it provides several effective paths that are in line with the development of vocational education in the Greater Bay Area by constructing a highly efficient and synergistic system of vocational education and by promoting the development of regional economic integration.